Structure determination of a new fluorescent tricyclic nucleoside from archaebacterial tRNA. - McCloskey, J A (1987)
A highly fluorescent nucleoside was detected in enzymatic digests of the extremely thermophilic archaebacterium Sulfolobus solfataricus by combined liquid chromatography-mass spectrometry (LC/MS). Following isolation, the structure was determined primarily by mass spectrometry, to be 3-(beta-D-ribofuranosyl)-4,9-dihydro-4,6,7-trimethyl-9-oxoimidazo[ 1, 2-a]purine (mimG), a new derivative of the Y (wye) nucleoside. The structural assignment was verified by comparison of the base released by acid hydrolysis with the corresponding synthetic base, using mass spectrometry, chromatography, and UV absorption and fluorescence properties. Nucleoside mimG was also detected by LC/MS in hydrolysates of the thermophiles Thermoproteus neutrophilus and Pyrodictium occultum. These results constitute the first finding of a member of the hypermodified Y family of nucleosides in archaebacteria.